Social sustainability in the UAE: Towards a comprehensive and sustainable development model - Almutawa, Ayesha; Alsuwaidi, Sharifa; Almesafri , Aaesha; Al Adeedi, Ayesha (Research Journal in Advanced Humanities, 2025)
This study aims to explore the reality of Social Sustainability in the United Arab Emirates, in light of National Trends towards building a comprehensive and sustainable development model that takes into consideration Social Dimensions alongside economic and Environmental Issues. The study’s importance, however, is mainly attributed to its direct connection to the “UAE Vision 2031,” which places humans and quality of life at the core of its Evolution Policies, necessitating a deep understanding of Social Values, Justice, and Community Participation in achieving sustainable development. We should note, however, that the current study has adopted a Descriptive-Analytical Approach, using a questionnaire as the primary technique for data collection from a sample of 300 individuals representing the Emirati community, which was randomly selected. The collected data have been analyzed using descriptive statistical methods, through which the respondents’ awareness level regarding Social Sustainability has been carefully measured to evaluate people’s satisfaction with government policies and Initiatives. The results, after all, have shown a high realization of family cohesion and social justice, in addition to positive satisfaction with the state efforts exerted in the Fields of Health, Education, and Housing. However, there is an urgent need to enhance Community Participation in decision-making processes. Accordingly, and in light of these results, the study has developed a set of recommendations and proposals, the most prominent of which are. Integrating Social Sustainability Concepts into Educational Curricula; Developing National Indicators to measure Social Performance periodically, and promoting the partnership between the Public Sector and Civil Society in the implementation of Community-Oriented Programs and Initiatives; Encouraging initiatives related to supporting women and youth; and Leveraging digital transformation to enhance Community Communication and achieve greater comprehensiveness in development.